Vermicompost process as treatment of organic waste generated in vegetables - da Rosa , Liciane Oliveira; de Souza, Karine Fonseca; Costa, Maiara Moraes; Martins, Gabriel Afonso; Coelho, Caren Wilsen Miranda; Burin, Paula; Fick, Rubiane Buchweitz; Mendes, Ana Clara Marins; Corrêa, Luciara Bilhalva; Corrêa, Érico Kunde (Seven Editora, 2023)
The objective of the work was to deal with the organic waste generated in the horticultural sector by the vermicomposting process, which results in vermicomposting. An experiment was carried out in 10l plastic boxes, where organic waste generated in a food distribution trade, organic fertilizer, and earthworms of the Eisenia fetid species were added. After setting up the experiment, monitoring of temperature and internal and ambient humidity was carried out, and monthly collections for laboratory analysis were carried out, as well as at the end of the process, the earthworms were counted, which were classified into young and adult. The values of temperature, pH, electrical conductivity, and humidity for the three treatments were within the limit recommended by scientific articles and current legislation for this type of process, as well as the reproduction of earthworms, which went from 40 adult individuals initially, to five times more of that value at the end of the process. Thus, it is possible to state that vermicomposting is a viable alternative for the treatment of waste, as it generates a product with agronomic and environmental value. doi: https://doi.org/10.56238/devopinterscie-052